Energy/people/buildings : making sustainable architecture work - Kimpian, Judit; Hartman, Hattie; Pelsmakers, Sofie (London : RIBA Publishing, 2021)
Energy performance feedback is an essential tool in addressing the current climate crisis.00However, this is not simply another theoretical text about energy performance in buildings. This book is for anyone who wants to better understand how energy is used in buildings, and how to drive down operational energy use ? whether you?re an architect, student, client, building services engineer, contractor, building operator or other stakeholder. Focusing on evidence from feedback on buildings in use, it explains what it takes to get them to perform as expected, as well as the reasons why they often fail.00'Energy, People, Buildings' draws extensively on the findings of studies, UK government-funded building performance evaluations and on original research into seven case studies from across the UK and abroad that have achieved exemplary energy use through building performance feedback.00Providing a clear roadmap to understanding aspects that impact building users? comfort and satisfaction, it also outlines the factors behind energy use and how to track it across the life of a project to ensure that your building performs as intended.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable architecture; Sustainable architecture -- Case studies; Sustainable buildings